2006
DOI: 10.4103/0972-9941.27735
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic surgery for inguinal hernia: Current status and controversies

Abstract: Repair of inguinal hernia is one of the commonest operations performed by surgeons around the world. The treatment of this common problem has seen an evolution from the pure tissue repairs to the prosthetic repairs and in the recent past to laparoscopic repair. The fact that so many hernia repairs are practiced is a testimony to the fact that probably none is distinctly superior to the other. This review assesses the current status of surgery for repair of inguinal hernia and examines the various controversial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Laparoscopic hernia repair can be done by two methods -Trans Abdominal Pre Peritoneal (TAPP) and Totally Extra Peritoneal (TEP). 1 Both these methods have their advantages and disadvantages. In TEP mesh is placed in the extra peritoneal space which is fixed by various fixation devices, so that it does not get displaced leading to recurrence of post-operative complications.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic hernia repair can be done by two methods -Trans Abdominal Pre Peritoneal (TAPP) and Totally Extra Peritoneal (TEP). 1 Both these methods have their advantages and disadvantages. In TEP mesh is placed in the extra peritoneal space which is fixed by various fixation devices, so that it does not get displaced leading to recurrence of post-operative complications.…”
Section: Introductionmentioning
confidence: 99%
“…Bhandarkar S et al, in his study reported that the wound infection rates were significantly lower after laparoscopic techniques (1%) than after the Lichtenstein operation (2.7%) and other open mesh repairs (2.4%). The incidence of inguinal hematoma was found to be significantly lower after the laparoscopic repairs (13.1%) than after the Lichtenstein repair (16.0%) as well as with the other open mesh techniques (14.3%) (21) . Erhan et al conducted a study and reported 4-6% of patients having chronic pain after Lichtenstein and preperitoneal hernia repair (22) and Poobalan et al…”
Section: Discussionmentioning
confidence: 93%
“…In TAPP the surgeon goes into the peritoneal cavity and places a mesh through a peritoneal incision over possible hernia sites. TEP is different as the peritoneal cavity is not entered and mesh is used to seal the hernia from outside the thin membrane covering the organs in the abdomen (the peritoneum) [49].…”
Section: Discussionmentioning
confidence: 99%